2008
DOI: 10.1016/j.saa.2007.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence quenching of versatile fluorescent probes based on strongly electron-donating distyrylbenzenes responsive to aromatic chlorinated and nitro compounds, boronic acid and Ca2+

Abstract: The fluorescence quenching behavior of two distyrylbenzenes (DSBs) newly prepared bearing strongly electron-donating groups was investigated. Several chlorinated and nitro compounds quench the fluorescence of both DSBs with various efficiencies depending on the electron-withdrawing properties; the strongly electron-withdrawing compound, such as 2,4,5-trichlorophenol and 2,4-dinitrofluorobenzene, effectively diminish the fluorescence intensities of the DSBs. Since the fluorescence quenching constants and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…[53] Motoyoshiya et al reported distyrylbenzenes based derivative 40 linked with an electron donating group for the binding of Ca 2 + ions ( Figure 13). [54] In THF, 40 showeds trong emission at 485 nm (F = 0.51). However, upon incremental addition of Ca 2 + ions into the solution of receptor 40 resulted in the decrease of fluorescencei ntensity.T his was ascribed to the binding of Ca 2 + ions with azacrown ether moiety.I na ddition to these examples, dinuclearc alcium complexes of oxa-azamacrocyclic receptors have also been reported.…”
Section: Crown Ether/azacrown Ether Based Probesmentioning
confidence: 98%
See 1 more Smart Citation
“…[53] Motoyoshiya et al reported distyrylbenzenes based derivative 40 linked with an electron donating group for the binding of Ca 2 + ions ( Figure 13). [54] In THF, 40 showeds trong emission at 485 nm (F = 0.51). However, upon incremental addition of Ca 2 + ions into the solution of receptor 40 resulted in the decrease of fluorescencei ntensity.T his was ascribed to the binding of Ca 2 + ions with azacrown ether moiety.I na ddition to these examples, dinuclearc alcium complexes of oxa-azamacrocyclic receptors have also been reported.…”
Section: Crown Ether/azacrown Ether Based Probesmentioning
confidence: 98%
“…Motoyoshiya et al. reported distyrylbenzenes based derivative 40 linked with an electron donating group for the binding of Ca 2+ ions (Figure ) . In THF, 40 showed strong emission at 485 nm ( Φ =0.51).…”
Section: Crown Ether/azacrown Ether Based Probesmentioning
confidence: 99%
“…This color enhancement could be attributed to “through bond energy transfer” (TBET) phenomenon . The absence of fluorescent property of probe P3 was attributed to the presence of highly electron withdrawing nitro groups which will quench the fluorescence of probe P3 …”
Section: Sensing Of Cationsmentioning
confidence: 99%
“…[60][61][62] These and a number of other properties have recently made 1,4-distyrylbenzenes attractive objects for the creation of photoactive materials: organic light-emitting diodes, materials for solar batteries, nonlinear optical materials and chemical sensors. [63][64][65][66][67][68] The first representative of bis-crown 1,4-distyrylbenzenes, bis(15-crown-5)-1,4-distyrylbenzene (3i), was obtained earlier, [69] using the Wittig-Horner reaction by condensation of bisphosphonate 5 with 4'-formylbenzo-15-crown-5-ester 6i under the action of 85 % aqueous KOH solution when refluxing in benzene with a yield of 53 %. One of the drawbacks of this approach, discovered when reproducing the procedure, was the need for additional purification of 3i by recrystallization from dioxane, which resulted in a significant decrease in yield.…”
Section: Bis-styrylbenzenes Containing Two Crown Ether Moietiesmentioning
confidence: 99%